(untitled) (Scientific journal of the Fergana State University, 2025)
The article provides a comparative analysis of word formation through affixation in Uzbek and English. It examines the morphological, semantic, and functional aspects of affixation, as well as its connection to national thinking and linguocultural factors. The similarities and differences in affixation processes within the lexical systems of both languages are identified and illustrated with examples.